Why social media use is so attractive among young people in the 21st century? - Çınar, Selin (Brazilian Journal of Science, 2023)
Social media is another indispensable communication tool of this era. There are approximately three billion social media users in the world, and these users spend at least two hours a day on platforms. It is certain and indisputable that social media has an important place in our lives. In particular, emerging trends especially attract the attention of the "Z generation" (those born in 2000 and after). Young people who try the trends that appear on screen in an effort to become phenomena lead their lives according to the ideals of others. So, the goal of this research is to examine the psychological effects of social media using behavior. Because the effect of social media is seen even in the way young people who spend time in front of their phones and tablets speak, in their movements, and in their attitudes towards their family and friends. In addition, analyzing which factors make social media attractive to the young population. Because when young people are socializing—that is, when they follow new trends, make friends, and discover the events around them—this research paper will present which events or influences make them more attractive on social media.